2009
DOI: 10.1111/j.1365-2621.2009.01966.x
|View full text |Cite
|
Sign up to set email alerts
|

Acceleration of ageing in rice stick noodle sheets using low temperature

Abstract: The objectives of this research were to study the effects of temperature and time on ageing of rice stick noodle sheet retrogradation, and to estimate the effect of accelerated ageing on the eating qualities of the noodles. Hardness was used as a textural index due to a good correlation between instrumental and sensory evaluation. The hardness of aged sheets significantly increased as a function of time, except at 30°C ageing. Examination of cut surfaces of fresh sheets revealed a network formation, but the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
0
9
1
Order By: Relevance
“…First, during cooling and undercooling which range in this sample from 10 to À7.5°C, the gel temperature fell slowly (0.3°C/min) which allowed amylose chains to retrograde to the highest extent as revealed by the presence of the thickest matrix around the ice crystals. In fact, several investigations have reported that low temperature accelerates retrogradation of starch gels or starch-based foods (Lin and Chein, 1995;Czuchajowska et al, 1998;Satmalee and Charoenrein, 2009). Second, although high undercooling is usually associated with a high nucleation rate (Reid, 1983) and consequently results in numerous small ice crystals (Miyawaki, 2001;Petzold and Aguilera, 2009), this phenomenon was not observed in this experiment.…”
Section: Frozen Structurecontrasting
confidence: 54%
“…First, during cooling and undercooling which range in this sample from 10 to À7.5°C, the gel temperature fell slowly (0.3°C/min) which allowed amylose chains to retrograde to the highest extent as revealed by the presence of the thickest matrix around the ice crystals. In fact, several investigations have reported that low temperature accelerates retrogradation of starch gels or starch-based foods (Lin and Chein, 1995;Czuchajowska et al, 1998;Satmalee and Charoenrein, 2009). Second, although high undercooling is usually associated with a high nucleation rate (Reid, 1983) and consequently results in numerous small ice crystals (Miyawaki, 2001;Petzold and Aguilera, 2009), this phenomenon was not observed in this experiment.…”
Section: Frozen Structurecontrasting
confidence: 54%
“…Starch retrogradation is the re-organization of amylose and amylopectin macromolecules in the gelatinized starch to the new crystalline structure (Mestres et al, 1988). Generally, the rice noodle is kept at room temperature during the ageing step to let starch retrogradation occur (Satmalee & Charoenrein, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…network in the noodle (Seib, Liang, Guan, Liang, & Yang, 2000). The hardness and tensile strength of rice noodle increases mainly during the ageing step due to starch retrogradation (Satmalee & Charoenrein, 2009). Furthermore, Yu, Ma, and Sun (2009) reported that the increase in starch retrogradation was positively correlated with the increase in the hardness of cooked rice.…”
Section: Samplementioning
confidence: 97%
See 1 more Smart Citation
“…Retrogradation can lead to an obvious increase in the firmness of stored baked goods [ 2 ] and frozen cooked rice [ 3 ], making them unattractive to consumers. However, in some products, retrogradation can provide a desirable quality such as in the manufacture of rice stick noodles [ 4 ], resistant starch type 3 [ 5 ] croutons, and bread crumb [ 6 ]. For this reason, numerous studies have been performed to examine the factors affecting the retrogradation of starch.…”
Section: Introductionmentioning
confidence: 99%